Historical museums in innovative tourism activities in Ukraine - Lysiuk, Tatiana V. (Universit of Technology in Katowice Press, 2024)
The article examines Ukrainian historical museums, which are currently developing in difficult conditions due to economic difficulties caused by limited funding for museum activities. The conditions for the use of innovative digital technologies in the work of museum institutions are analysed. The process of digitalisation of museums and its role in the work of modern museology in terms of attracting tourists, which is inseparable from the socio-cultural function of the museum space, are described. It is determined that under the influence of the latest trends in museology, which have shifted the focus from museum objects to the socio-cultural needs of visitors, society’s requirements for the communication capabilities of museums have increased. In the context of information and technological development, in addition to traditional forms, modern ways of interaction between museums and society are emerging in the form of three-dimensional technologies, including creative video screenings, panoramic projection, virtual reality and animation technologies.
Keywords: Ukrainian; museum; historical museums; tourism; innovative tourism; animation technologies